Access to Modern Energy Services in Ukraine during the Wartime - Yuliia Vashchenko (Bratislava Law Review)
The right to access to modern energy services is a crucial precondition for the realisation of the majority of human rights and freedoms. The energy sector is one of the strategic sectors of each country. Currently, the energy sector of Ukraine is among the key military targets during the full-scale aggression of the Russian Federation in Ukraine. Disconnections in energy services caused by the military attacks (both cyber and physical) negatively influence the life of the peoples in Ukraine. Therefore, the protection of the right to access to modern energy services at all levels is among the key tasks of the public administration in Ukraine. This paper aims at the analysis of the legal issues of the encouragement of the right to access to modern energy services in Ukraine under the war of aggression conditions and elaboration of the possible solutions for the public administration.